Financing Of Terrorism Crime Between The International Agreements And Syrian Legislation - أحمد بسام; رجب رواد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
To eliminate terrorism we must first eliminate the factors that help it grow, and the first of these factors is the financing, whereas the United Nations Agreement For The Suppression Of The Financing Of Terrorism pointed in its prologue to the positive correlation between the power and capability of the terrorist groups and their economic power. Subsequently suppression of terrorism financing became the most important step to the international society and national legislations. So, it’s very important to get to know the meaning of financing terrorism from the concept of the national society and Syrian legislation, specially after the terrorism that Syria is going through, and getting to know the stages of the Syrian legislation’s improvement in this field.